2021
DOI: 10.1038/s41388-021-02055-2
|View full text |Cite
|
Sign up to set email alerts
|

A highly annotated database of genes associated with platinum resistance in cancer

Abstract: Platinum-based chemotherapy, including cisplatin, carboplatin, and oxaliplatin, is prescribed to 10-20% of all cancer patients. Unfortunately, platinum resistance develops in a significant number of patients and is a determinant of clinical outcome. Extensive research has been conducted to understand and overcome platinum resistance, and mechanisms of resistance can be categorized into several broad biological processes, including (1) regulation of drug entry, exit, accumulation, sequestration, and detoxificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 146 publications
(175 reference statements)
1
69
0
1
Order By: Relevance
“…One limitation of this study is that the limited number of patients represented in the study likely does not represent all the heterogeneous mechanisms underlying clinical resistance to platinum compounds. 13 Future studies with more patients will be required to determine whether the findings in our study are generalizable to all HGSOC tumors or only specific subclasses. Additionally, our preclinical models do not capture the influence of the immune system and tumor microenvironment on platinum responsiveness.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…One limitation of this study is that the limited number of patients represented in the study likely does not represent all the heterogeneous mechanisms underlying clinical resistance to platinum compounds. 13 Future studies with more patients will be required to determine whether the findings in our study are generalizable to all HGSOC tumors or only specific subclasses. Additionally, our preclinical models do not capture the influence of the immune system and tumor microenvironment on platinum responsiveness.…”
Section: Discussionmentioning
confidence: 91%
“… 113 Platinum resistance is a major determinant of survival, particularly in OCs, which are frequently diagnosed at late stage. Decades of literature demonstrate that resistance is multifactorial, 12 , 13 and there has been no clinical translation of biomarkers to predict platinum response or treatments to overcome platinum resistance, and these remain unmet clinical needs. To date, no study using modern proteogenomic technologies has been undertaken to characterize cancer cell responses to platinum or to understand mechanisms of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New studies are raising more and more questions nowadays about the mechanism based on chemotherapy resistance. Researches found that the primary mechanisms of platinum resistance included drug accumulation, the ability of DNA or RNA repair efficiency, and self-detoxification of cells ( 11 ). Of those, reduction in drug accumulation is one of the most generally acknowledged mechanisms of acquired OXA resistance ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The list of 4255 DEGs and 14,529 DMPs detected in our panel of OC cell lines was compared with the platinum response-related gene list (937 genes/proteins) recently curated by Huang et al [ 51 ]. We found 254 DEGs and 142 DMPs overlapping with the database entries ( Table S5 ).…”
Section: Resultsmentioning
confidence: 99%